Assessment of Endocrine-Disrupting Properties in Cosmetic Ingredients: Focus on UV Filters and Alternative Testing Methods - Adriana Solange Maddaleno (Cosmetics, 2025)
Endocrine-disrupting chemicals are substances capable of interfering with hormonal systems, potentially leading to adverse developmental, reproductive, neurological, and immune effects in both humans and wildlife. Various experimental models are currently available to assess the endocrine-disrupting potential of substances. However, in the context of cosmetic ingredients, the ban on animal testing for safety and efficacy evaluations in Europe and other regions necessitates the use of in vitro or in silico approaches. Concerns have been raised regarding the possible endocrine-disrupting properties of certain cosmetic compounds, prompting the development of a priority substance list that includes several ultraviolet (UV) filters. This review provides a comprehensive overview of the main methodologies employed to evaluate endocrine-disrupting effects, with a particular focus on different endocrine organs. It also compiles and analyzes literature data related to commonly used UV filters such as benzophenones, avobenzone, homosalate, octocrylene, octinoxate, and 4-methylbenzylidene camphor. A major limitation identified is the lack of validated in vitro methods for assessing disruptions in specific endocrine organs, such as the thyroid and pancreas. This gap hinders accurate interpretation of experimental results and highlights the urgent need for further research to clarify the safety profiles of UV filters and other cosmetic ingredients.